'Mad Dog?' Samuel Huntington and the Vietnam War. Issue 1 (23rd February 2018) - Gawthorpe, Andrew J.
ABSTRACT: Harvard professor Samuel P. Huntington has frequently been considered a Vietnam War hawk. His observation that 'forced-draft urbanization' might help the United States win the war has come to define his engagement in contemporary strategic debates. This essay argues that both Huntington's academic work and his private policy advice to the U.S. Government in fact urged a political settlement to the conflict. It argues that in spite of this, Huntington refused to break publicly with the U.S. policy because of his wider concern over what he saw as a crisis of authority in the U.S. foreign policy and governing institutions in the era.